Climate warming-driven changes in the flux of dissolved organic matter and its effects on bacterial communities in the Arctic Ocean: A review - Nguyen, Hien Thi; Lee, Yung Mi; Hong, Jong Kuk; Hong, Seongjin; Chen, Meilian; Hur, Jin (Frontiers in Marine Science, 2022)
The warming of the Arctic Ocean impacts the dissolved organic matter (DOM) imports into the Arctic region, which affects the local bacterial communities. This review addressed the current status of DOM inputs and their potential influences on bacteria data (e.g., population, production, and metabolic activity of bacteria), as well as the projected changes of DOM inputs and bacterial communities as a result of climate warming. Microbial communities are likely affected by the warming climate and the transport of DOM to the Arctic Ocean. Imported DOM can alter Arctic bacterial abundance, cell size, metabolism, and composition. DOM fluxes from Arctic River runoff and adjacent oceans have been enhanced, with warming increasing the contribution of many emerging DOM sources, such as phytoplankton production, melted sea ice, thawed permafrost soil, thawed subsea permafrost, melted glaciers/ice sheets, atmospheric deposition, groundwater discharge, and sediment efflux. Imported DOM contains both allochthonous and autochthonous components; a large quantity of labile DOM comes from emerging sources. As a result, the Arctic sea water DOM composition is transformed to include a wider range of various organic constituents such as carbohydrates (i.e., glucose), proteinaceous compounds (i.e., amino acid and protein-like components) and those with terrigenous origins (i.e., humic-like components). Changes to DOM imports can alter Arctic bacterial abundance, cell size, metabolism, and composition. Under current global warming projections, increased inflow of DOM and more diverse DOM composition would eventually lead to enhanced CO2 emissions and frequent emergence of replacement bacterial communities in the Arctic Ocean. Understanding the changes in DOM fluxes and responses of bacteria in the Arctic broadens our current knowledge of the Arctic Ocean’s responses to global warming.